KONSEP PENDIDIKAN ROHANI SEBAGAI UPAYA PENGELOLAAN MENTAL ANAK - Maslani, Maslani; Fitriyani, Annisa; Purnama, Asep; Salma, Ananda; Surya Abdi, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The importance of education in the family actually lies in the formation of spiritual educational values, especially through teaching religion to children because religious education has a major role in shaping a person's perspective on life. The aim of this research is firstly to provide an understanding of the definition of spiritual education, secondly aims to provide an understanding of the concept of spiritual education according to the Hadith of Rasululloh SAW as an effort to manage children's mental health. The research method used is library research. The results of this research are that spiritual education actually starts from the smallest environment of life, namely the family environment, how family and parental influence become the main spearheads of children's spiritual education before these children enter the outside world with more complex relationships and life problems. Therefore In the early stages of a child's education, parents should not make mistakes in providing education to them, because this will have an impact in the future, especially on the child's own mental state.